Music students' perceptions about the teaching residency program (2022–2024): a case study at Federal University of Piauí (Orfeu, 2026)
This paper aims to discuss the perceptions of undergraduate Music students from Federal University of Piauí about teaching work at school, through their performances in the Pedagogical Residency Program (2022/2024). With a qualitative approach of a single case study (YIN, 2010), the research was developed through interviews with residents who had their first experience working in basic education, in the Art curricular component, through the Pedagogical Residency. To analyze the material resulting from the undergraduate students' speeches, an adaptation of systematic steps of coding and categorization of the Grounded Theory (STRAUSS; CORBIN, 2008), originally Grounded theory (GLASER; STRAUSS, 1967), was used. When discussing the residents' perspective on formative aspects and theory/practice relationships developed during the Program, it was found that the teacher's performance must be configured to consider the context of their area within the basic school space, crossing human elements within the possibilities of teaching music at school. Furthermore, the work confirms the importance of the Residency in the professional preparation of students, also providing an insight into their perceptions about their undergraduate training in light of their participation in the Program.
Keywords: Perceptions of teaching work; Pedagogical Residency Program; Music teacher training